2018
DOI: 10.1007/s00253-018-8966-9
|View full text |Cite
|
Sign up to set email alerts
|

Robust signal peptides for protein secretion in Yarrowia lipolytica: identification and characterization of novel secretory tags

Abstract: Upon expression of a given protein in an expression host, its secretion into the culture medium or cell-surface display is frequently advantageous in both research and industrial contexts. Hence, engineering strategies targeting folding, trafficking, and secretion of the proteins gain considerable interest. Yarrowia lipolytica has emerged as an efficient protein expression platform, repeatedly proved to be a competitive secretor of proteins. Although the key role of signal peptides (SPs) in secretory overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 45 publications
0
58
0
Order By: Relevance
“…Since it was earlier reported that hydrophobicity and secondary structure are the key factors determining efficiency of the pre-sequence in driving the nascent polypeptide translocation and specifying the translocation mode (Yaver et al 1992; Matoba and Ogrydziak 1998), we used a panel of computational tools to study these parameters in the analyzed secretory elements. However, we could not see any straightforward correlation between the average hydrophobicity and the final extracellular abundance of the reporters (Celińska et al 2018). Correspondingly, neither calculated D-score values (reflecting probability of being recognized and processed by signal peptidase) nor predicted secondary structure could provide the key or support the rules governing the observed results.…”
Section: Engineering Secretory Capacity Of Yarrowia Lipolyticamentioning
confidence: 74%
See 2 more Smart Citations
“…Since it was earlier reported that hydrophobicity and secondary structure are the key factors determining efficiency of the pre-sequence in driving the nascent polypeptide translocation and specifying the translocation mode (Yaver et al 1992; Matoba and Ogrydziak 1998), we used a panel of computational tools to study these parameters in the analyzed secretory elements. However, we could not see any straightforward correlation between the average hydrophobicity and the final extracellular abundance of the reporters (Celińska et al 2018). Correspondingly, neither calculated D-score values (reflecting probability of being recognized and processed by signal peptidase) nor predicted secondary structure could provide the key or support the rules governing the observed results.…”
Section: Engineering Secretory Capacity Of Yarrowia Lipolyticamentioning
confidence: 74%
“…Enhanced production of the targeted, secretory protein may be achieved by several different strategies, including (i) engineering the DNA coding sequence itself, (ii) modification of a genetic construct structure, (iii) optimization of culturing conditions, and (iv) engineering molecular mechanisms of protein synthesis and secretion pathway (Graf et al 2009; Liu et al 2012). Within each of the proposed strategies, various solutions have been proposed, and some of them were conducted in Y. lipolytica , like (i) optimization of codon usage within the coding sequence (Celińska et al 2015; Celińska 2015; Dulermo et al 2017), (ii) amplification of the gene copy number, manipulation with regulatory elements contained in the genetic construction, mainly promoter (Le Dall et al 1994; Gasmi et al 2011b; Gasmi et al 2011a; Gasmi et al 2012; Dulermo et al 2017; Larroude et al 2018), (iii) bioprocess engineering, optimization of cultivation conditions (Chang et al 1998; Kim et al 2000; Nicaud et al 2002; Celińska et al 2017a), and (iv) co-synthesis of chaperones, manipulation with protein folding, and maturation mechanisms, engineering secretory tags (De Pourcq et al 2012; Celińska et al 2018). Nevertheless, the vast majority of studies on enhanced production of secretory proteins in Y. lipolytica was focused on strategies from (i) to (iii), while the approaches directing secretory pathway were largely neglected.…”
Section: Engineering Secretory Capacity Of Yarrowia Lipolyticamentioning
confidence: 99%
See 1 more Smart Citation
“…Y. lipolytica strains, bearing separately either SoAMY or TlGAMY genes under the control of strong promoter, secreted the recombinant proteins to the cultivation medium (Celińska et al 2018). In this experiment, crude medium supernatants were directly used as enzymatic preparations for hydrolysis of starch, without any purification procedures.…”
Section: Resultsmentioning
confidence: 99%
“…The example presented here demonstrates that top-performing transformants can be screened in one step. Previously, we used a smaller version of this toolkit to illustrate the assembly of an entire pathway, notably the carotenoid pathway (Celinska et al, 2017;Celi nska et al, 2018;Larroude et al, 2018), and the construction of a set of expression cassettes containing multiple secretion signal sequences, which allows the optimization of protein secretion (Celi nska et al, 2018;Soudier et al, 2019). Here, we have greatly expanded the capacity of our system, and we now provide strong as well as inducible promoters.…”
Section: Discussionmentioning
confidence: 99%